Amrith in the Late Phoenician Period - Al-Maqdissi, Michel; Ishaq, Eva (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
Presentation of the state of our archaeological documentation resulting from the excavations carried out by Nessib Saliby in Amrith during the late Phoenician period. At the same time, the study of the current topography of monuments published since the first action led by Ernest Renan in 1860-1861. The results of the analysis provide confirmation that Amrith during the late Phoenician period and the Hellenistic period did not constitute the statue of a city because it remained dependent on Arados and that the conclusion published in 1864 that (Marathus ne fut qu’une banlieue d’Aradus) still remains valid.